Intensified distortion: investment decisions with endogenous contracts and time inconsistency - Li, Yanzhao (2024)
Previous studies on investment decisions with endogenous contracts typically adopt differences among discount rates to describe decision makers’ impatience. Yet evidences from behavioral economics and neuroeconomics suggest that decision makers are impatient with short-term choices, but patient with long-term choices. Using quasi-hyperbolic discounting and real options agency framework, we investigate the effect of this time-vary impatience, i.e., time-inconsistent preference, on compensation contracts and investment triggers. We reveals that time inconsistency does not affect the dominance of restricted stock, but intensifies agency conflicts between the manager and shareholders. Our study provides a new perspective for understanding underinvestment and high equity incentives.